Exploiting the application of l-aptamer with excellent stability: an efficient sensing platform for malachite green in fish samples. Issue 14 (12th June 2019) - Luo, Xiaowei; Chen, Zhifeng; Li, Hongfeng; Li, Wenqin; Cui, Liang; Huang, Jiahao
Abstract : Effective monitoring of the content of malachite green (MG) in aquaculture is of great importance for food safety. Abstract : Effective monitoring of the content of malachite green (MG) in aquaculture is of great importance for food safety. Traditional methods for MG assay, such as chromatography and spectroscopy, have been criticized for expensive instrumentation and complicated pretreatments. An MG RNA aptamer (MGA) is a powerful tool for immediate and rapid detection of MG. However, RNA is easily degraded by nucleases and is unstable in the environment, making accurate and reliable detection of MG difficult. In order to address the problems, an innovative levo (l )-MGA with excellent stability is designed to perform the specific recognition function. Interestingly, the gel electrophoresis and fluorescence measurement results indicate that this unnaturally occurringl -aptamer is resistant to nuclease degradation and it can be kept intact in the standard buffer solution under room temperature for quite a long time. A label-free, simple, and efficient method has been developed for sensitive detection of MG in fish tissue, which holds promising potential in food analysis and environmental monitoring.